Strategi Pemasaran Lembaga Pendidikan untuk Meningkatkan Jumlah Peserta Didik di PG/TK Samarinda - Abrori, Maskub (SYAMIL: Journal of Islamic Education, 2015)
Educational institutions authorized to manage education which used in this institutions, included manage learning methods, learning materials, student activities, and introduced to society. A while ago educational institutions as a produce education service only seen as seller’s market, prospective students compete to enroll in school without much competition with other institutions. The marketing strategy is needed in introducing educational institutions that is to inform effective and efisien to people about education services so people can attract to study in this institutions. This study aims to know the factors that influence marketing strategy in educational institutions and to know what the best marketing strategy to use in PG/TK Islam Bunayya Samarinda. This study use qualitative research methods with field research. The methods are indepth interview, observation and documentation. The data analysis used SWOT analysis. This study results are 1) implementation of marketing strategy that used by PG/TK Islam Bunayya Samarinda are direct and indirect methods, 2) internal factors consist of strengths are the teachers, services and communication, tution fee, and curriculum, then for the weaknesses are double work, education background of teachers, location, parking area. External factors consist of opportunities are muslim majority, expectation to study in the next study, cooperation with others institutions, alumnus supports, and people perceptions about Islam school, 3) marketing strategy that can be used in PG/TK Islam Bunayya Samarinda is stable growth strategy.